If Anti-Racism Is the Goal, Then Anti-Oppression Is How We Get There - Smith, Carmela Fusciello; Aguilar, Jemel P.; Kozu, Shuei; D'Angelo, Karen A.; Keenan, Elizabeth King; Tomczak, Stephen Monroe (Advances in Social Work, 2022)
Many schools of social work around the United States of America wrote anti-racism statements because of the recent murders of Black and Brown people. In this contribution, the authors describe a challenging and tense discussion of racism and anti-racism leading to a group process about oppression and anti-oppression in the social work profession. For some, the urgency to address racism led to tactics and strategies that got in the way of social workers engaging in anti-oppressive practices. While the structure of higher education often reinforces traditional hierarchies of power, the profession of social work calls us to promote our core values of social justice, integrity, and the importance of human relationships as we strive for an anti-oppressive future. Consequently, social work faculty may experience role conflict as we navigate these tensions. We believe it is important to harness and process such discomfort as we critically examine the power dynamics within our own department, and our own profession. This voluntary, ad hoc group, composed of a diverse group of faculty members, provides space for ongoing mutual aid, consciousness raising, appropriate discomfort, and accountability. If anti-racism is the goal, then anti-oppression is how we get there.
0 citations (Crossref) [2023-10-31] Number: 2
Keywords: White supremacy; dept.swk; peer-reviewed

Well-Being and Prosperity: Multidirectional Disciplinary Interactions with Religion - Morais, M.; Karakunnel, J.J.; Perumbilly, S.; Yeon, G.; Rassendren, G. (Journal of Dharma, 2022)
Despite significant advancements in science and technology, religion continues to influence human lives. The twentieth-century perspectives from social sciences, influenced by the secular hypothesis, mainly highlight the negative influence of religion on human progress and practically ignore its influential and positive impact on various fields of knowledge/disciplines. In this paper, we have examined literature from politics, economics, and psychology to understand religion’s impact on these disciplines and vice versa. We find that religion’s contribution to human society in the 20th and 21st centuries has been mostly positive, especially in education, healthcare, social justice, economic growth, ethics, and initiatives for eradicating inequality and injustice. For instance, religion provides effective coping measures and strategies when humans face uncertainties and catastrophes and facilitate comfort, confidence, and emotional wellness. Further, we realised that (i) the contemporary research literature in social sciences generally highlights the interaction between religion and various fields of knowledge in a unidirectional way —i.e., religion influencing disciplines and not how disciplines influence religion, and (ii) that it fails to reveal a more complex multidirectional and circular relationship between religion and social sciences. This paper proposes ways to bring together social scientists and religious scholars to facilitate the much-needed discussion on the multidirectional relationship between religion and social sciences, thereby paving the way toward the well-being of individuals and social transformation. © 2022 Journal of Dharma: Dharmaram Journal of Religions and Philosophies (DVK, Bangalore),.
Keywords: and well-being; charitable giving; circularity; dept.mft; linearity; peer-reviewed; political participation; religion; sustainable development; ⛔ No DOI found

Stress, Marginalization, and Disruption: A Qualitative Rapid Situational Assessment of Substance Users and HIV Risk in Lebanon - Khoshnood, Kaveh; Smoyer, Amy B.; Maviglia, Francesca; Kara, Janine; Khouri, Danielle; Fouad, Fouad M.; Heimer, Robert (International Journal of Environmental Research and Public Health, 2022)
Lebanon is a diverse and dynamic nation of six million people that has experienced considerable disruption for the last two decades. The Syrian Civil War, which began in 2011, resulted in the displacement of 1.1 million Syrians to Lebanon. Today, Lebanon is the country with the largest per capita number of refugees in the world. In addition, the country experienced a social, economic, and political crisis in 2019 that destabilized the entire society-circumstances that were further complicated by COVID-19 pandemic. With all of the competing calamities in Lebanon, there has been limited scientific investigation into substance use and the risk of HIV infection among the country's population. To address this gap in knowledge, a qualitative rapid situational assessment (RSA) of substance use and risk of HIV infection in and around Beirut, the nation's capital, was conducted. The goal of this analysis is to describe the demographics and drug use patterns of this population, explore their HIV knowledge and risks, and build knowledge about their perceptions of and access to substance use treatment and other social services.
0 citations (Crossref) [2023-10-31]
Keywords: COVID-19; Drug Users; HIV Infections; HIV risk; Health Services Accessibility; Humans; Lebanon; Pandemics; Refugees; Stress; Psychological; Substance-Related Disorders; dept.swk; peer-reviewed; rapid situational assessment; refugees; substance use

The Origin and Evolution of the Term “Social Work” - Luquet, W.; Tomczak, S.M. (Journal of Sociology and Social Welfare, 2022)
The origin of the term “social work” has long been misattributed to the 1907 work of economist Simon Patten. While Patten’s contribution to social work is important, though mostly forgotten, the term had been used long before regarding the work of nuns and settlement workers. Quoting archival and historical findings, this article traces the origin, evolution, and widespread use of the term “social work.” The words of the early founders of social work are utilized to tell the story of how the work of persons doing “the social work” of the church or settlement evolved into the name of the profession. These shifts in terminology in social work’s early history have influenced the subsequent direction of the field up to the present day. © 2022, Western Michigan University. All rights reserved.
Keywords: Simon Patten; dept.swk; history; peer-reviewed; profession; settlements; social work; ⛔ No DOI found

The Impact of Spirituality and Religious Practice on Senior Living Leader Career Resilience - Myers, Dennis R.; Rogers, Robin K.; Garrison, Brianna V.; Singletary, Jon E.; Groce, Haley (Journal of Applied Gerontology, 2022)
Experienced senior living leaders (SLLs) report the impact of spirituality and religious practice on SLL role adaptation and continuation. The sample included 18 SLLs in 18 skilled care settings representing public, non-profit, and for-profit types of incorporation, with oversampling of for-profit facilities. The average years of SLL experience was 24 years. In-depth interviews were examined through a thematic analysis approach using Excel software. Seventy-eight percent described how a higher power, religious beliefs, and faith practices were associated with their role. Their narratives revealed three major themes: Frame (calling and pre-dispositional spiritual beliefs and religious practices), Role Performance (how spirituality informed SLL administrative practice), and Benefits (perceived rewards of adherence to spiritual beliefs and practices). Further analysis of the three themes produced codes that added greater specification for each theme. Implications provided for normalizing the spirituality and work-life intersect and infusing ethical integration of spirituality and work-life in SLL educational programs.
1 citations (Crossref) [2023-10-31]
Keywords: adminstration; career resilience; dept.swk; faith and work; peer-reviewed; religious practices; skilled care; spirituality

The ins and outs of posttraumatic growth in children and adolescents: A systematic review of factors that matter - Ferris, Cheyenne; O'Brien, Kyle (Journal of Traumatic Stress, 2022)
Posttraumatic growth (PTG) refers to a positive psychological change that occurs following a seismic and highly challenging life circumstance. An individual who experiences PTG reports posttrauma development that surpasses their baseline level of pretrauma function in various domains. The present systematic review of the current literature aimed to explore factors related to the development of PTG in children and adolescents exposed to trauma. Included studies investigated a range of factors that impact PTG development in youth from five countries: the United States, Israel, China, Japan, and Norway. Studies addressed multiple types of traumatic experiences, including medical trauma, war- and terror-related trauma, and environmental trauma. Findings suggested that factors that impact the development of PTG include the presence of posttraumatic stress symptoms, specifically intrusiveness, and cognitive factors, such as the use of positive reappraisal and deliberate rumination. Many factors demonstrated inconsistencies across studies, such as the impact of age, gender, social support, and parent factors. The findings from this systematic research study encourage the notion that certain clinical intervention strategies, such as deliberate rumination, positive reappraisal coping strategies, and trauma-informed group therapy, may facilitate growth in trauma survivors. Future research should test if these intervention strategies directly impact growth and whether there is an evidence-based form of intervention that can assist clinicians in taking a growth- and strengths-based perspective after trauma.
4 citations (Crossref) [2023-10-31] _eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1002/jts.22845
Keywords: dept.swk; peer-reviewed

Effect of a brief social contact video on transphobia and depression-related stigma among adolescents: A randomized clinical trial - Amsalem, D.; Halloran, J.; Penque, B.; Celentano, J.; Martin, A. (JAMA Network Open, 2022)
Importance: Transphobia and stigma remain barriers to seeking mental health care for gender-diverse adolescents. Objective: To examine the utility of brief social contact-based video interventions of transgender protagonists with depression to reduce transphobia and depression-related stigma and increase treatment-seeking intentions among adolescents in the general population. Design, Setting, and Participants: During August 2021, a total of 1437 participants were recruited and randomly assigned to 1 of 4 video-based conditions in a 2:2:1:1 ratio: (1) transgender adolescent girls, (2) transgender adolescent boys, (3) cisgender adolescent girls, or (4) cisgender adolescent boys. Interventions: In each of the approximately 110-second videos, an empowered presenter shared their personal story about coping with depression and reaching out for help. Main Outcomes and Measures: The primary outcome was the score on the Attitudes Toward Transgender Men and Women (ATTMW) scale. Secondary outcomes were (1) a "gender thermometer" rating for warmth in transgender perception, (2) the Depression Stigma Scale (DSS) score, and (3) the General Health-Seeking Questionnaire (GHSQ) score. Results: Of the 1437 randomized participants, 1098 (76%) completed the postintervention assessment and passed all the validity tests (mean [SD] age, 16.9 [1.2] years; 481 [44%] male; 640 [58%] White). A significant change in attitudes toward transgender youth was found within the intervention group only (mean [SD] ATTMW scores: intervention group, 34.6 [23.1] at baseline to 32.8 [24.2] after intervention; P ¡.001; control group, 33.5 [23.4] at baseline to 32.4 [24.1] after intervention; P =.01). The mean (SD) total DSS scores decreased significantly across study groups (intervention: 1.3 [3.3]; control: 1.7 [3.3]; P ¡.001). A significant increase in intention to seek help from a parent was found in the intervention (mean [SD] GHSQ score, 0.2 [1.1]) and control (mean [SD] GHSQ score, 0.3 [1.2]) groups (P ¡.001), as was a decrease in those not wanting to seek help from anyone (mean [SD] GHSQ score: intervention, 0.2 [1.6], P =.009; control, 0.3 [1.2], P ¡.001) Secondary analyses revealed significant differences in baseline ATTMW scores and intervention effects between transgender and gender-diverse and cisgender participants and between lesbian, gay, bisexual, or queer (LGBQ) and straight participants (F = 36.7, P ¡.001) and heterosexual participants (F = 37.0, P ¡.001). A significant difference was also found in mean (SD) transgender warmth scores from baseline to after intervention between groups (2.6° [13.1°] in the intervention group vs 0.4° [8.3°] in the control group; P ¡.001). Conclusions and Relevance: In this randomized clinical trial, brief social contact-based videos proved efficacious in reducing transphobia and depression-related stigma and in increasing treatment-seeking intentions among adolescents in the general population. By personifying, individualizing, and providing face and voice to the experience of transgender youth, other adolescents, especially those who are cisgender and/or of a heterosexual orientation, can gain empathetic insights into the lives of their often marginalized and stigmatized fellow youth. Trial Registration: ClinicalTrials.gov Identifier: NCT04969003. © 2022 Collabra: Psychology. All rights reserved.
10 citations (Crossref) [2023-10-31] tex.art_number: e220376 tex.document_type: Article tex.pubmed_id: 35212749 tex.source: Scopus
Keywords: Adolescent; Depression; Female; Humans; Male; Patient Acceptance of Health Care; Prejudice; Social Stigma; Transgender Persons; Video Recording; adolescent; controlled study; depression; dept.mft; dept.swk; female; human; male; patient attitude; peer-reviewed; prejudice; psychology; randomized controlled trial; social stigma; transgender; videorecording

Do monetary incentives undermine performance on intrinsically enjoyable tasks? A field test - Esteves-Sorenson, Constança; Broce, Robert (The Review of Economics and Statistics, 2022)
Economists have long been intrigued by an influential literature in psychology positing that monetary pay lowers performance on enjoyable tasks by crowding out agents’ intrinsic interest in them. But typical experiments in this literature do not report a full set of performance metrics, which might reveal conflicting evidence on crowding out. Further, they may suffer from confounds. To evaluate these issues, we review over 100 prior tests and run a field experiment building on the canonical two-session test for crowding out wherein agents receive pay for an interesting activity in session 1 that is withdrawn unexpectedly in session 2. We test whether pay harms performance using a comprehensive set of performance measures, and if so, whether unmet pay expectations might also contribute to this decline. Our results on output, productivity and quits are most consistent with a standard economics model than with a crowding-out one. Additional, though more speculative, evidence suggests that unmet pay expectations may harm output quality. © 2020 The President and Fellows of Harvard College and the Massachusetts Institute of Technology.
2 citations (Crossref) [2023-10-31] tex.document_type: Article tex.source: Scopus
Keywords: dept.swk; peer-reviewed